All-optical driven soft crawler with complex motion capabilities - Chenchu Zhang; Jin Wang; Linhan Zhao; Renfei Chen; Qiangqiang Zhao; Jie Zhao; Fating Liu; Yucheng Bian; Heng Zhang; Yisen Wang; Chaowei Wang; Ying Hu (International Journal of Smart and Nano Materials, 2024)
The emergence of millimeter-scale soft actuators has significantly expanded the potential applications in areas such as search and rescue, drug delivery, and human assistance, due to their high flexibility. Despite these advancements, achieving precise control over the intricate movements of soft crawlers poses a significant challenge. In this study, we have developed an all-optical approach that enables manipulation of propulsive forces by simultaneously modifying the magnitude and direction of friction forces, thereby enabling complex motions of soft actuators. Importantly, the approach is not constrained by specific actuator shapes, and theoretically, any elongated photothermal actuator can be employed. The actuator was designed with an isosceles trapezoid shape, featuring a top width of 2 mm, a bottom width of 4 mm, and a length of 8 mm. Through our manipulation approach, we showcase a proof-of-concept for complex soft robotic motions, including crawling (achieving speeds of up to 2.25 body lengths per minute), turning, avoiding obstacles, handling and transferring objects approximately twice its own weight, and navigating narrow spaces along programmed paths. Our results showcase this all-optical manipulation approach as a promising, yet unexplored tool for the precision and wireless control for the development of advanced soft actuators.